Assessing potential shared genetic aetiology between body mass index and sleep duration in 142, 209 individuals. Issue 2 (26th November 2018) - Garfield, Victoria; Fatemifar, Ghazaleh; Dale, Caroline; Smart, Melissa; Bao, Yanchun; Llewellyn, Clare H.; Steptoe, Andrew; Zabaneh, Delilah; Kumari, Meena
Abstract: Observational studies find an association between increased body mass index (BMI) and short self‐reported sleep duration in adults. However, the underlying biological mechanisms that underpin these associations are unclear. Recent findings from the UK Biobank suggest a weak genetic correlation between BMI and self‐reported sleep duration. However, the potential shared genetic aetiology between these traits has not been examined using a comprehensive approach. To investigate this, we created a polygenic risk score (PRS) of BMI and examined its association with self‐reported sleep duration in a combination of individual participant data and summary‐level data, with a total sample size of 142, 209 individuals. Although we observed a nonsignificant genetic correlation between BMI and sleep duration, using LD score regression ( r g  = −0.067 [ SE  = 0.039], P  = 0.092) we found that a PRS of BMI is associated with a decrease in sleep duration (unstandardized coefficient = −1.75 min [ SE  = 0.67], P  = 6.13 × 10 −7 ), but explained only 0.02% of the variance in sleep duration. Our findings suggest that BMI and self‐reported sleep duration possess a small amount of shared genetic aetiology and other mechanisms must underpin these associations.